Development of a brownfield inventory for prioritizing funding outreach in Tucson, Arizona - Theresa Foley (Taylor & Francis Group, 2021)
Fear of liability from the 1980 Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA or Superfund) has prompted developers to build preferentially upon undeveloped green space rather than potentially contaminated former industrial sites, leading to urban sprawl in the suburban areas while blighted properties in the urban core remain vacant. A brownfield is defined as a property in which the presence or potential presence of a hazardous substance or contaminant poses a barrier to development. Agencies often create brownfield inventories by performing a site suitability analysis, using distinguishing features such as ecologically and culturally significant areas or neighborhoods that need revitalizing. Pima County, Arizona and the Sonora Environmental Research Institute, Inc. (SERI) developed a brownfield inventory of the large, industrial area directly to the west of Davis-Monthan Air Force Base. Because the brownfield target area has few residential neighborhoods and lacks the distinguishing features usually used in a brownfield site suitability analysis, the county and SERI used the official tax assessor database and 11 federal, state and county environmental databases to develop a brownfield inventory. The goal of the project was to prioritize properties that stood to benefit from the grant funding. The final brownfield inventory contained 531 parcels.